THE IMPROVEMENT OF STUDENT LEARNING OUTCOMES USING DISCOVERY LEARNING MODEL FOR ELEMENTARY SCHOOL STUDENTS - Ari Novendra; Taufina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the low student learning outcomes in grade 4 of SD Negeri 21 Bandar Buat City of Padang. This causes learning outcomes has not optimally achieved. The purpose of this study was to describe the improvement of student learning outcomes in Civics learning by applying the Discovery Learning learning model to fourth grade students of SD Negeri 21 Bandar Buat City of Padang. This type of research was CAR using a qualitative and quantitative approach. This research was conducted in grade 4 of Semester 1 in 2019/2020 school year. The results showed an increase in learning plan, namely cycle I gained a percentage of 89% (good) and cycle II obtained a percentage of 96% (very good).Tthe learning outcomes of students in the first cycle gained a percentage of 75% (enough) then the percentage increased to 85% (good) in the second cycle. Thus, Civics learning by applying the Discovery Learning model can improve Civics learning outcomes of fourth grade students of SD Negeri 21 Bandar Buat City of Padang